Microdiscectomy and Translaminar Approach: Mini-Invasiveness and Posterior Elements Conservation Relevance. (May 2014) - Vanni, D.; Sirabella, F. S.; Pantalone, A.; Galzio, R.; Salini, V.; Magliani, V.
Introduction: Interlaminar approach represents the standard procedure for lumbar disc herniation surgical treatment. In case of cranial or lateral fragment migration into the neuroforamen (hidden zone), it is necessary to perform partial or total arterectomy to remove the herniated material, thus leading to iatrogenic vertebral instability risk. Materials and Methods: Since January 2010, 40 patients with lumbar disc herniation and with disc fragment migration into the "hidden zone" underwent microdiscectomy by translaminar approach. Using a micro high-speed cutter, a 8 ± 2 mm fenestration at the level of affected side hemilamina was performed, displaying the involved root and removing the disc fragment. A clinical follow-up at months 1, 3, 6, and 12 was performed by mean of the Visual Analog Scale (VAS) and the Oswestry Disability Index (ODI). A radiographic control at months 1, 6, and 12 was obtained (dynamic radiographic studies in last two times). Results: In over 60% of cases, L4-L5 was the disk involved. Roots visualization was successfully achieved through translaminar approach. There was no need to associate neither partial or complete arterectomy nor flavectomy. An intraoperative bleeding occurred only in 5% of cases, as a consequence of an epidural veins involvement, treated through local hemostasis (Avitene) and without surgery time prolongation (mean duration 60 ± 10 minutes). There were no dural injuries. Patients showed an immediate and lasting radicular symptoms resolution. There was no need to perform revision surgery. Dynamic radiographic studies at months 6 and 12 did not detected instabilities. Conclusion: Surgical microdiscectomy allowed us to successfully treat patients affected by lumbar disc herniation. Low back pain treatment and disc-root conflict resolution must be done conservatively avoiding iatrogenic instability risk. In case of cranial or lateral fragment migration into the neuroforamen, because a partial or total arterectomy could be requested for herniated disc fragment removal, this is not always possible. A conservative and minimally invasive approach, which allows to resolve disc-root conflict without affecting spine stability, represents a crucial technique. The translaminar approach is an anatomical, effective, and minimally invasive technique, suitable in cases of lumbar disc herniations with disc fragment migration into the hidden zone. It can be performed in all lumbar segments, not involving posterior elements (both bony and ligamentous ones), which are necessary for spine stability. In case of proper indications, this technique is more effective than the standard one because it allows symptoms relief, faster recovery times, less postoperative pain, and reduction in iatrogenic instability risk. Disclosure of Interest None declared References Papavero L, Kothe R. The translaminar approach for cranially extruded lumbar disc herniations. Oper Orthop Traumatol 2013;25(1):6–15 Seiz M, Pechlivanis I, Bag S, Schmieder K, Thome C, Tuettenberg J. [Translaminar fenestration for caudally herniated lumbar discs—a technical note]. Z Orthop Unfall 2009;147(5):597–599 Choi KC, Kim JS, Ryu KS, Kang BU, Ahn Y, Lee SH. Percutaneous endoscopic lumbar discectomy for L5-S1 disc herniation: transforaminal versus interlaminar approach. Pain Physician 2013;16(6):547–556